2018
DOI: 10.3390/s18020508
|View full text |Cite
|
Sign up to set email alerts
|

H∞ Robust Control of a Large-Piston MEMS Micromirror for Compact Fourier Transform Spectrometer Systems

Abstract: Abstract:Incorporating linear-scanning micro-electro-mechanical systems (MEMS) micromirrors into Fourier transform spectral acquisition systems can greatly reduce the size of the spectrometer equipment, making portable Fourier transform spectrometers (FTS) possible. How to minimize the tilting of the MEMS mirror plate during its large linear scan is a major problem in this application. In this work, an FTS system has been constructed based on a biaxial MEMS micromirror with a large-piston displacement of 180 µ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…whereβ > 0 and m > 0 are tuning parameters. In (6), P is the positive definite solution of (A + BF )…”
Section: A Nominal Control Design Using Optimal Composite Nonlinear mentioning
confidence: 99%
See 1 more Smart Citation
“…whereβ > 0 and m > 0 are tuning parameters. In (6), P is the positive definite solution of (A + BF )…”
Section: A Nominal Control Design Using Optimal Composite Nonlinear mentioning
confidence: 99%
“…The robust control for micromirrors has gained significant attention in recent years, and various research works have been reported. H ∞ robust control has been proposed for a large-piston MEMS micromirror-based compact fourier transform spectrometer systems [6]. The closed-loop system maintains good stability and robustness under various driving conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various MEMS concepts for optical path-length scanning have been reported, typically targeting an out-of-plane translation with large stroke required for the classical dual-beam Michelson interferometer FTS set-up, consisting of fixed and moving mirrors (here realized by an MOEMS) and an optical beam splitter. For large-stroke out-of-plane translation of the MEMS mirror, different actuation principles have been investigated so far: electrostatic [ 5 , 6 , 7 , 8 ], piezoelectric [ 9 , 10 , 11 ], magnetic [ 12 , 13 , 14 , 15 ], and electrothermal [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], typically using resonant operation for larger strokes, e.g., [ 7 , 8 , 11 ], but also using quasi-static actuation, e.g., [ 10 , 17 ]. Most of these different MOEMS actuation mechanisms suffer from limitations in spectral resolution due to parasitic effects of MEMS-based path-length modulation: first of all, mirror tilt [ 11 , 17 , 19 ], deformation of the mirror due to dynamically (owing to inertia) or statically (due to mirror suspension or optical coating) induced mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…Microelectromechanical system (MEMS) scanners with large vertical actuation of both the micromirror and microlens have a wide range of applications, including optical pickup [1], multiphoton microscopy [2], Fourier transform spectrometry [3,4], confocal microscopy [5], optical coherence tomography [6], and micro optical diffusion sensing [7][8][9]. MEMS scanners based on electrostatic [2,7,10,11], piezoelectrical [12], and electromagnetic [13] actuation mechanisms can achieve high-speed scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with electrostatic, piezoelectrical, and electromagnetic actuations, an electrothermal MEMS scanner can achieve large displacement (several hundred micrometers) without resonant operation. To date, various novel designs for electrothermal MEMS scanners with vertical out-of-plane actuation have been proposed [3][4][5][6]8,[14][15][16]. For example, Zhang et al [14] presented a lateral shift-free actuator design using three bimorph hinges and two multimorph segments to compensate for the lateral shift.…”
Section: Introductionmentioning
confidence: 99%